Multiplexed suspension array immunoassays for detection of antibodies to pneumococcal polysaccharide and conjugate vaccines - Dunbar, Sherry A. (Frontiers in Cellular and Infection Microbiology, 2023)
Combination and polyvalent vaccines not only provide protection against several different pathogens at the same time but can also increase vaccine protection against pathogens that have closely related pathogenic strains or serotypes. Multiplexed serological testing is a preferred method for determining the efficacy of combination and polyvalent vaccines, as it reduces the need for conducting multiple individual assays to confirm immune responses and cross-reactivity, uses less sample, and can be faster, more reliable, and more cost-effective. Bead-based suspension array technologies, such as the Luminex ® xMAP ® Technology, are often used for development of multiplexed serological assays for various vaccine trials and for routine testing in clinical laboratories to determine immune status of vaccinated individuals. This article reviews publications describing the development and implementation of bead-based multiplexed serological assays for detection of immune responses to polyvalent polysaccharide and conjugate vaccines against Streptococcus pneumoniae. Many of these serological assays on the bead array platform have been further optimized and expanded over time and are still widely used today.